Food value chain transformation in developing regions - Reardon, Thomas; Minten, Bart (International Food Policy Research Institute, 2021)
In this chapter, for brevity, we focus on the output value chains, but the conceptual framework and most trends are also relevant to the input value chains, the lateral service value chains, and R&D&E suppliers. Output value chains in developing countries have transformed over the past 50 years but particularly quickly only in the past 25 years. In many countries the transformation of value chains has been abrupt, not gradual. Reardon and Timmer (2014), illustrating with Asian evidence, explain the drivers of this rapid change as a confluence of the following three sets of interlinked transformations: 1. Downstream demand side change (urbanization and diet change) “pulling” system transformation. 2. Midstream/downstream change (in the structure and conduct of retail, wholesale, logistics, and processing) “intermediating” system transformation. 3. Upstream change (intensification, diversification, and commercialization of farming) “feeding” system transformation.